2016
DOI: 10.1093/alcalc/agw031
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine, Liver Function Derangement and Brain Atrophy in Alcoholics

Abstract: Hyperhomocysteinemia has been described in alcoholics and may be related to brain atrophy, a reversible condition with an obscure pathogenesis. We studied 59 patients and found that liver function derangement, vitamin B12 and homocysteine levels are all independently related to brain atrophy assessed by computed tomography, although we found no association between these parameters and cognitive alterations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Hyperhomocysteinaemia and vitamin B12 deficiency are often detected in patients affected with diseases associated with neuropathy such as diabetes, 66 alcoholism, 67 Parkinson’s disease (treated with L‐dopa), 68 or HIV infection 69 . Vitamin B12 deficiency could be a modifiable risk factor for neuropathy in those patients.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperhomocysteinaemia and vitamin B12 deficiency are often detected in patients affected with diseases associated with neuropathy such as diabetes, 66 alcoholism, 67 Parkinson’s disease (treated with L‐dopa), 68 or HIV infection 69 . Vitamin B12 deficiency could be a modifiable risk factor for neuropathy in those patients.…”
Section: Discussionmentioning
confidence: 99%
“…Both conditions were significantly more frequent in the subgroup of LHON patients with B12 deficiency. Patients with excessive alcohol consumption are known to represent a high-risk group for vitamin deficiency, including B12 deficiency [ 47 ]. Using multivariate analysis, we confirmed that excessive alcohol consumption is a significant predictor for LHON disease status and for B12 deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, we may have underestimated the true prevalence of B12 deficiency in the LHON subgroup with excessive alcohol consumption: Not only serum B12 may be falsely elevated in subjects with excessive alcohol consumption [ 47 50 ], but also they present with hyperhomocysteinemia [ 47 ]. It is unclear whether subjects with excessive alcohol consumption, normal serum B12, and increased tHCy have a true vitamin B12 deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…3 Higher values, up to 80%, were reported when brain computed tomography (CT) was blindly evaluated by an expert radiologist. 4 Brain atrophy in alcoholics mainly depends on white matter atrophy, 5 although gray matter atrophy, at least affecting the frontal lobe, has also been described. 6 These changes are associated with the amount of ethanol consumed 7,8 and are partially reversible with abstinence.…”
Section: Introductionmentioning
confidence: 99%